Analysis of the potential for the use of artificial peat soil based on oil sludge - Polina K. Semyantseva; Angela A. Ilchenko (RUDN Journal of Ecology and Life Safety)
Oil sludge is one of the dangerous sources of environmental pollution, which causes significant damage to ecosystems. The technologies used for their disposal do not show efficiency, these data are confirmed by the authors’ SWOT analysis of the existing method of waste data management - sludge accumulation. The paper considers a new technological solution for processing oil sludge into artificial peat soil. The study describes the process of obtaining artificial peat from oil sludge, the main characteristics and properties of the resulting material. The authors present the results of laboratory studies: assessment of the physico-chemical characteristics of artificial peat soil, such as its density, humidity, organic matter content, concentration of heavy metals and other harmful substances, as well as an experiment on the study of fertile properties. An analysis of the potential and possibility of introducing this material into practice was also carried out. The findings can be useful for further research and development in the field of oil sludge utilization and processing and improving the environmental sustainability of peat soils.